Carbon Monoxide Measuring System using MQ-7 Sensor with Cloud Storage - Irfan Muhammad Zaqi; - Yohandri; - Yulkifli; Nofi Yendri Sudiar (Department of Physics – Universitas Negeri Padang UNP, 2023)
Carbon monoxide (CO) gas cannot be detected by sight or smell but is highly detectable and is formed from incomplete combustion such as in motor vehicles. Currently monitoring CO gas levels and measurement data at any time cannot be accessed all the time. Therefore, a measuring instrument system with data storage is required. We developed an instrument to measure CO gas levels in the air. The system developed uses the MQ-7 and ESP8266 sensors to produce a CO gas level measurement device with Cloud Storage. This research is a type of engineering research. The measurement technique used is a direct and indirect measurement. The direct measurement technique is done by comparing CO level data from standard tools with measuring instruments. Indirect measurement techniques are carried out by analyzing the data. Based on the research objectives, the specifications of the work tools are the average accuracy percentage of 97.27%, and the precision of 97.31%. Based on these result, the CO gas level measuring tool has a measurement accuracy and precision of close to 100%. So it is concluded that the CO level measuring tool can work properly